2001
DOI: 10.1148/radiographics.21.4.g01jl091025
|View full text |Cite
|
Sign up to set email alerts
|

Do Computers Teach Better? A Media Comparison Study for Case-based Teaching in Radiology

Abstract: A prospective study was performed to better define the role of computers in teaching radiology to medical students. Two hundred twentyfive 3rd-year students were randomly assigned to one of four groups and exposed to 10 radiology cases as well as to a voluntary weekly radiology lecture. Group A used computer-based cases with interactive elements; group B used computer-based cases without interactive elements; group C used paper-based cases with interactive elements; and group D was not exposed to the cases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
72
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 30 publications
7
72
0
3
Order By: Relevance
“…Several other studies have reported similar findings with Zou et al reporting that the majority of students preferred teaching with interactive dialogues, preferably in small groups with students volunteering to answer questions 13 . However, a certain degree of basic knowledge is required to facilitate discussion and this may be more efficiently covered prior to small group tutorials in didactic lectures or via online resources.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Several other studies have reported similar findings with Zou et al reporting that the majority of students preferred teaching with interactive dialogues, preferably in small groups with students volunteering to answer questions 13 . However, a certain degree of basic knowledge is required to facilitate discussion and this may be more efficiently covered prior to small group tutorials in didactic lectures or via online resources.…”
Section: Discussionsupporting
confidence: 76%
“…Despite the volume of evidence to support the mainstream integration of Radiology into the medical curriculum, there is a paucity of research in relation to the use of small group tutorials as a method of teaching Radiology. Small group tutorials are an interactive form of teaching with many studies reporting a strong student preference for teaching with interactive case based discussions 13 . Malek et al reported improved enjoyment and concentration with significantly better learning outcomes when using cased based teaching in Radiology 14 .…”
Section: Introductionmentioning
confidence: 99%
“…This finding is similar to that of Cook who found that residents who completed web-based modules on clinical topics that contained case-based multiple choice questions had higher immediate post-test scores (Cook et al 2006). Maleck also found that medical students studying radiology, who did a computer-based program which included cases with interactive elements such as multiple choice and text-based questions, performed better on a multiple choice test than students who read the cases only with no interactive elements (Maleck et al 2001). Our study concerns non-clinical topics but confirms that instructional methods that actively engage learners requiring application of the knowledge improve learning.…”
Section: Discussionsupporting
confidence: 66%
“…However, the literature is mixed and learning preference and learning styles are not consistently associated with academic performance. [17][18][19]31 In one study, significant improvement in performance did not persist after a delay of several months, although learning platform differences were seen immediately after the training. 15 One plausible explanation for our finding of no difference is that testing occurred 2 weeks after the lectures were presented.…”
Section: Discussionmentioning
confidence: 96%
“…8,15 The effectiveness of adding self-assessment questions and feedback to a content delivery platform are mixed. [16][17][18][19] In fall 2005, both the traditional video and 4-panel platforms were employed in a second-year pharmacotherapy course. This pilot study compared students' preferences and academic performance using the 2 platforms.…”
Section: Introductionmentioning
confidence: 99%